Big data and global trade law - Burri, Mira (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
"7.60bData has been conceptualized as the 'new oil' and although this is a flawed statement, it catches well the high value attached to data as a driver of economic growth and innovation, and as a force of change in all facets of societal life. The implications of data and data analytics are multiple and some of them can be far-reaching. At a micro-level, for instance, the value of data changes the traditional relationship between consumers and producers. While in the past, companies sold products to their customers in return for money and some negligible data, 'today, transactions and indeed every interaction with a consumer produce valuable information. Sometimes the data itself is so valuable that companies such as Facebook, LinkedIn, Pinterest, Twitter, and many others are willing to offer free services in order to obtain it'. Data has also become essential in terms of competition and market power. Some firms, like Apple, Google, Amazon, Facebook, Microsoft or Baidu, have had a sizeable first-mover advantage in the field and become 'analytics leaders', while at the same time establishing themselves as some of the most valuable companies in the world, as they benefit from double-sided markets. The capacity to handle data has increasingly turned into a competitive advantage not only for companies but also for countries and plays out as a power move in the global political economy. For instance, China unveiled in 2016 that it is in possession of the world's fastest supercomputer, which was 40 times more powerful than the fastest computer of 2010, only to be overcome by the United States in the following years by two IBM-built supercomputers. The ongoing battle between China and the US with regard to 5G dominance is equally revealing. Overall, companies as well as governments are increasingly encouraged to use the potential of data and to mobilize their resources aptly, so as to make the data-driven economy real f7.60"--
Data flows and global trade law / Mira Burri -- Data flow-related provisions in preferential trade agreements : trends and patterns of diffusion / Manfred Elsig and Sebastian Klotz -- The costs of data protectionism / Martina Ferracane -- WTO law and cross-border data flows : an unfinished agenda / Andrew D. Mitchell and Neha Mishra -- Artificial intelligence and trade / Anupam Chander -- Blockchain's practical and legal implications for global trade and global trade law / Emmanuel Ganne -- TRIPS meets big data / Daniel J. Gervais -- Big data, AI, and border enforcement of intellectual property rights : impact on trade flows / Xavier Seuba -- Futuring digital privacy : reimaging the law/tech interplay / Urs Gasser -- The algorithmic learning deficit : artificial intelligence, data protection, and trade / Svetlana Yakovleva and Joris Van Hoboken -- Panta rhei : a European perspective on ensuring a high-level of protection of human rights in a world in which everything flows / Kristina Irion -- Data regulation with Chinese characteristics / Henry S. Gao -- Regulatory convergence of data rules in Latin America / Rodrigo Polanco Lazo -- Uploading CPTPP and USMCA provisions to the WTO's digital trade negotiations poses challenges for national data regulation : example from Canada / Patrick Leblond -- Data ownership and data access rights : meaningful tools for promoting the EU digital single market? / Florent Thouvenin and Aureliatamò-Larrieux -- Data is different, so policymakers should pay close attention to its governance / Susan A. Aaronson.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: World Trade Organization; Transborder data flow -- Law and legislation; Big data; Data protection -- Law and legislation; Foreign trade regulation; Blockchains (Databases) -- Law and legislation; Artificial intelligence -- Law and legislation